Ipragliflozin, a sodium–glucose cotransporter 2 inhibitor, reduces bodyweight and fat mass, but not muscle mass, in Japanese type 2 diabetes patients treated with insulin: A randomized clinical trial. Issue 4 (21st January 2019) - Inoue, Hideka; Morino, Katsutaro; Ugi, Satoshi; Tanaka‐Mizuno, Sachiko; Fuse, Keiko; Miyazawa, Itsuko; Kondo, Keiko; Sato, Daisuke; Ohashi, Natsuko; Ida, Shogo; Sekine, Osamu; Yoshimura, Masahiro; et al.
Abstract: Aims/Introduction: Sodium–glucose cotransporter 2 inhibitors reduce bodyweight (BW) by creating a negative energy balance. Previous reports have suggested that this BW reduction is mainly loss of body fat and that ~20% of the reduction is lean mass. However, the effects of sodium–glucose cotransporter 2 inhibitors on BW and body composition remain unclear. We examined these effects in Japanese patients with type 2 diabetes mellitus treated with insulin. Materials and Methods: In this open‐label, randomized controlled trial, 49 overweight patients (body mass index ≥23 kg/m 2 ) with inadequate glycemic control (hemoglobin A1c >7.0%) receiving insulin treatment were randomly assigned to receive add‐on ipragliflozin or no additional treatment (control group). Patients were followed for 24 weeks. The goal for all patients was to achieve glycated hemoglobin <7.0% without hypoglycemia. The primary end‐point was a change in BW from baseline to week 24. Body composition was assessed with dual‐energy X‐ray absorptiometry and bioelectrical impedance analysis. Results: BW change was significantly larger in the ipragliflozin group than in the control group (−2.78 vs −0.22 kg, P < 0.0001). Total fat mass was reduced evenly in the arms, lower limbs and trunk in the ipragliflozin group. Total muscle mass and bone mineral content were maintained, but muscle mass in the arms might have been affected by ipragliflozin treatment. Conclusions: Ipragliflozin treatment for 24 weeks resulted in reduced BW, mainly from fat mass loss. Muscle mass and bone mineral content were maintained. Further study is necessary to elucidate the long‐term effects of ipragliflozin. Abstract : The administration of ipragliflozin for 24 weeks to insulin‐treated patients significantly reduced their bodyweight compared with the control group. Total muscle mass and bone mineral content were maintained, but the arms might have been affected by treatment with ipragliflozin.